Investigation of cream and ointment on antimicrobial activity of Mangifera indica extract - Amgad A Awad El-Gied; Abdelkareem M Abdelkareem; Elnazeer I Hamedelniel (Wolters Kluwer Medknow Publications, 2015)
Medicinal plants have curative properties due to the presence of various complex chemical substance of different composition, which are found as secondary plant metabolites in one or more parts of these plants. Mangifera indica Linn (MI L.) is a species of mango in the Anacardiaceae family. Phytoconstituents in the seed extracts may be responsible for the antimicrobial activity of the plant. The purpose of the study was to formulate and evaluate the antimicrobial herbal ointment and cream from extracts of the seeds of mango (MI L.) The formulated ointments containing oleaginous-based showed the best formulation compared to the emulsion water in oil type, the ointment and cream bases in different concentration 1%, 5% and 10%. The formulated ointment and cream of MI L. were subjected to evaluation of Uniformity of Weight, measurement of pH, viscosity, Spreadability, Acute skin irritation study, stability study and antimicrobial activity. Our study shows that MI has high potential as an antimicrobial agent when formulated as ointment and creams for topical use. Thus, the present study concludes that the formulated formulations of the MI are safe and efficient carriers, with potent antimicrobial activity.